Relevansi Profesionalitas, Kebijakan, dan Kompetensi Guru Pendidikan Agama Islam: Sebuah Tinjauan Kritis - Mauzifa, Mauzifa; Irawan, Andri; Rahman, Afrillia Muthia (QuranicEdu: Journal of Islamic Education, 2025)
This article aims to analyze the relevance of professionalism, policies, and competencies of Islamic Religious Education teachers in supporting the implementation of the Indonesian education system. (PAI) teachers in supporting the implementation of the education system in Indonesia. This research uses qualitative methods to determine how to find, collect, process, and analyze data, collect, process, and analyze data. The approach used is descriptive with document/text study, in which data is collected through documentation of various documents, including books, books, and other documents. documentation of various documents, including books, literature, and relevant scientific journals. relevant scientific journals. The results showed that the professionalism of PAI teachers professionalism, which includes attitudes, ethics, and pedagogical competence, greatly influences the effectiveness of education policy implementation. effectiveness of education policy implementation. However, this study also identified a number of challenges, such as the lack of policy understanding by teachers, unequal access to professional training programs and a suboptimal performance evaluation system. an unoptimized performance evaluation system. In addition, limited budget and resources exacerbate gaps in policy implementation in different regions. This article emphasizes the importance of synergizing education policies, professional development programs and teacher competencies to improve quality of learning. Policy implementation that involves school principals, parents and the school community is a strategic solution in strengthening teacher professionalism. teacher professionalism. The harmonious relationship between policy, professionalism, and competence of PAI teachers is crucial in creating an educational environment, and competence of PAI teachers is considered crucial to creating a positive educational environment.